Pengaruh Paham Liberalisme dan Neoliberalisme Terhadap Pendidikan Islam di Indonesia - M. Yunus Abu Bakar (TSAQAFAH, 2012)
This paper  is aimed at discussing the influence of liberalism dan neo-liberalism in Islamic Education  in  Indonesia.   The existence of  Islamic education  is always dealing with   and grappling with  the  reality  surrounding  them. The struggle between  Islamic education to meet socio-cultural reality are two possibilities: a. Islamic education gives impact on socio-cultural environment; b. Islamic education is influenced by the reality of social change, by socio-cultural environment. The  ideology of   liberalism and neo-liberalism, rationalism,  freedom,  responsibility,  fairness,  and  tolerance  are  ideals struggled  by liberalism, despite the fact that some ideal values  fail to realize. While neoliberalism is actually understood the existence of   liberal capitalism is the ideology of  liberalism that has  led to  the economic sector. The  influence of  not only  the political, social, and economic, but  in education as well which is a view that emphasizes the development of capabilities, to protect the rights and freedoms as well as identify problems and social change efforts in order to maintain stability for a long time. Central ideas of education revolves around the application  of   the  concept of   rationality,  freedom,  and equality. Education  is a democratic distribution of rationality with a balanced treatment, between freedom and equality of  rights and obligations, students. Teachers function as facilitators and change the  learning process. Philosophycally  running constructivism  learning  including  the development of  capitalization of   education in the form of  education commercialization. The fact also has affected in the world of Islamic education.